Analysis of comparable academic performance: panel logistic regression model - Radavičius, Marijus; Samusenko, Pavel (Lietuvos matematikos rinkinys, 2010)
Conditional logistic regression model is fitted to data of student academic performance. This enables one to compare difficulties of different examinations and to identify related factors.
Keywords: academic performance; binary item response; conditional logistic; IRT; nuisance parameters; Rasch model